Meconium-stained Amniotic Fluid and Newborn Respiratory Distress: A Case Report - Kashyap, Saurabh; Maralikar, Mukta; Jha, Deepak; Akbar, Md. (Indian Journal of Pharmacy Practice)
Meconium-Stained Amniotic Fluid (MSAF) and the resulting Meconium Aspiration Syndrome (MAS) present significant challenges in neonatal care. This case report illustrates the multifaceted approach to managing a newborn with MSAF and highlights the pathophysiology associated with MAS. The case involves a neonate born in emergency circumstances, emphasizing the importance of immediate intervention. Management, including respiratory support, ventilation, inhaled nitric oxide, antibiotics, and steroids, are discussed. While advances in obstetrical and neonatal care have reduced morbidity and mortality associated with MAS, the lack of standardized management guidelines in developing countries remains a concern.
Keywords: Meconium-stained amniotic fluid; Meconium aspiration syndrome; Fetal distress; Respiratory distress; Neonatal management